What's in Your Tropical Fruit? - Susan S. Percival; Brooke Findley (EDIS)
FSHN 07-08, a 6-page fact sheet by Susan S. Percival and Brooke Findley, discusses the nutritional values of lesser-known tropical fruits that may be of interest to growers in Florida, with an eye towards future research on and marketing of these fruits. Published by the UF Department of Food Science and Human Nutrition, September 2007.